2012
DOI: 10.1007/s00216-012-5731-2
|View full text |Cite
|
Sign up to set email alerts
|

Common wheat determination in durum wheat samples through LC/MS analysis of gluten peptides

Abstract: A method to detect the presence of common wheat in durum wheat flour samples was developed and tested. Flour samples, or ground wheat samples, were digested by pepsin and chymotrypsin, and the peptide mixture obtained was analyzed by LC/ESI-MS and LC/ESI-MS/MS, which led to the identification of two marker peptides. One peptide was coded only in the DD genome, and thus present only in common wheat; the second was present in all wheat samples (both common and durum), so it was used as marker of the total wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Emmer and durum wheat cultivars were all recognized by DQ2.5-glia-α1a-specific T-cell clones, but only two out of four emmer cultivars and three out of ten durum wheat cultivars activated DQ2.5-glia-α1b- and DQ2.5-glia-α2-specific T-cell clones37. Consistent with our results, Prandi et al 38. found that the 33-mer was not present in durum wheat.…”
Section: Resultssupporting
confidence: 91%
“…Emmer and durum wheat cultivars were all recognized by DQ2.5-glia-α1a-specific T-cell clones, but only two out of four emmer cultivars and three out of ten durum wheat cultivars activated DQ2.5-glia-α1b- and DQ2.5-glia-α2-specific T-cell clones37. Consistent with our results, Prandi et al 38. found that the 33-mer was not present in durum wheat.…”
Section: Resultssupporting
confidence: 91%
“…A marker peptide for common wheat was identified and semi‐quantified with a peptide common to both common and durum wheat. The method was calibrated with several common wheats‐ durum wheat mixtures at various percentages and also using different wheat varieties to average the natural variability …”
Section: Methodology Overview: Tricks and Tipsmentioning
confidence: 99%
“…Another approach was used for the characterization of the protein CM3 which is one of the major allergens of wheat, by using LTQ‐OrbiTrap analysis on peptides obtained from the enzymatically digested protein separated by gel electrophoresis . In this case, one of the identified peptides was used as a marker for quantification on UPLC/ESI‐MS by using its isotopically labeled analog as an internal standard, allowing to determine the protein amount in the different samples.…”
Section: Cerealsmentioning
confidence: 99%
“…Recently, Prandi and coworkers reported, for the first time, the application of electrospray ionization (ESI) coupled to liquid chromatography‐mass spectrometry (LC‐MS) for the determination of common wheat in durum wheat samples. To this aim, two peptide markers obtained from a double enzymatic digestion with pepsin (3 h at 37 °C) and chymotrypsin (4 h at 37 °C) have been monitored …”
Section: Introductionmentioning
confidence: 99%
“…To this aim, two peptide markers obtained from a double enzymatic digestion with pepsin (3 h at 37°C) and chymotrypsin (4 h at 37°C) have been monitored. [27] In the present work, an ultra-performance liquid chromatography (UPLC)-MS/MS methodology based on multiple reaction monitoring (MRM) has been developed for the fast detection of durum with common wheat contamination or adulteration. To this aim, a rapid extraction procedure of the puroindolineenriched protein fraction has been optimized.…”
Section: Introductionmentioning
confidence: 99%